1997
DOI: 10.1002/(sici)1097-0215(19970822)74:4<438::aid-ijc13>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

mdm2 mRNA expression is associated with survival in ovarian cancer

Abstract: Expression of mdm-2 mRNA was measured in 90 ovarian-cancer tissue specimens using the S1 nuclease assay, to investigate a possible association between MDM2 expression and prognosis. mdm-2 mRNA expression was an independent prognostic factor for patients with primary ovarian cancer, FIGO (International Federation of Gynecology and Obstetrics) stages III and IV (n 5 57), who all received chemother-apy with carboplatin or cisplatin and cyclophosphamide. Median survival time for patients (FIGO stages III and IV) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
6
13
0
5
Order By: Relevance
“…MDM2 mRNA expression was not associated with survival of any FIGO stage of ovarian cancer but was associated with the clinical outcome of FIGO stage III and IV patients (Tanner et al, 1997). Our present findings are similar to those of Tanner et al (1997), indicating that MDM2 mRNA expression is a favorable prognostic factor in NSCLC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…MDM2 mRNA expression was not associated with survival of any FIGO stage of ovarian cancer but was associated with the clinical outcome of FIGO stage III and IV patients (Tanner et al, 1997). Our present findings are similar to those of Tanner et al (1997), indicating that MDM2 mRNA expression is a favorable prognostic factor in NSCLC.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we tested whether the presence or absence of MDM2 mRNA was a suitable prognostic factor to predict the clinical outcome of NSCLC. To date, the use of MDM2 mRNA to predict the survival rate after chemotherapy has been reported only in ovarian cancer (Tanner et al, 1997). Our previous study (Wang et al, 1998) demonstrated high frequencies of deletion mutation in Taiwanese NSCLC and that this mutation was correlated with p53 immunostaining.…”
mentioning
confidence: 94%
“…Apart from these reports, the ring domain of MDM2 has been shown to induce growth arrest (23). Consistent with these observations, several laboratories reported that overexpression of MDM2 is a favorable prognostic marker in cancer (24)(25)(26)(27).…”
Section: Introductionsupporting
confidence: 59%
“…Although a higher mdm2 -mRNA expression was associated with a better prognosis in patients with ovarian carcinomas (24), several publications describe a correlation between a high HDM2 transcript level and poor outcome for different cancer patients (reviewed in ref. 23).…”
Section: Discussionmentioning
confidence: 99%